High-flame-retardant drum brake lining and preparation method thereof
By preparing heat-resistant flame-retardant pellets and using dense and rolling techniques to form a cladding structure, combined with multiple step-by-step molding processes, the problem of high-fire-retardant drum brake lining is easily caught in high temperature conditions. The product's high temperature stability and excellent flame retardant performance are achieved.
Patent Information
- Application Number
- CN202411286484.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing high-fire-retardant drum brake lining is prone to ignition under high temperature conditions, and economical flame-retardant materials are heat decomposed during hot press forming and thermal curing, resulting in product layering and bubbles, limiting their application.
Before preparing high flame retardant drum brake lining, heat-resistant flame retardant pellets are prepared, and a cladding structure is formed through intensive and roller processes to prevent the flame retardant water from being analyzed, combined with multiple step-by-step molding processes , ensure the stability of flame retardant materials at high temperatures.
It achieves no braking and ignition under high temperature conditions, reduces the ignition point of friction materials, improves the product's high temperature resistance and flame retardant performance, and meets the application needs of heavy-duty commercial vehicles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of brake linings, and in particular to a highly flame-retardant drum brake lining and a preparation method thereof. Background Art
[0002] With the rapid development of domestic commercial vehicles, especially the rapid development of the logistics and transportation industry, commercial vehicle fires caused by high brake temperature or brake locking have occurred from time to time, bringing great safety hazards to the transportation industry. The fundamental cause of brake fires is that long-term brake drag leads to high brake temperature (500-600℃), and at the same time, the organic matter in the friction material decomposes into small molecular free radicals, and the temperature reaches the ignition point of the friction material, generating open flames.
[0003] In order to solve the above problems and reduce the transportation safety risks, a new type of highly flame-retardant drum brake lining has emerged in the market. This friction material generally uses high-temperature resistant resins to improve its heat resistance, such as modified phenolic resins or polyimide resins, benzoxazine resins, or one or more mixtures. However, in long-term road tests with vehicles, it was found that the maximum braking temperature of the pneumatic drum brake, the chassis braking system of heavy-duty commercial vehicles, is as high as 580-600°C, which is much higher than the thermal decomposition temperature of the above-mentioned resins, especially in the long downhill sections of Yunnan, Guizhou and Sichuan in China. In order to curb the fire accidents caused by high braking temperature, one or more flame retardant materials must be added. Due to the particularity of the proportion, processing technology and working conditions of resin-based friction materials, halogen flame retardants are not suitable for use, and the cost of molybdenum and antimony flame retardant materials is relatively high. From an economic point of view, there are only a handful of flame retardant materials needed for development. Economical flame retardant materials such as hydrated aluminum hydroxide, magnesium hydroxide, and zinc borate are relatively cheap, but during the hot pressing and heat curing process with friction materials, due to the high temperature (hot pressing temperature 180-200°C, heat curing maximum temperature 200-220°C), the above economical flame retardant materials will decompose H2O molecules due to heat, resulting in a high instantaneous water vapor molecule content in the friction matrix material, causing stratification and bubbling of the hot pressed finished product and even causing the product to be scrapped, which greatly limits the application of economical flame retardant materials in the manufacture of drum brake linings.
[0004] Therefore, there is an urgent need for a production process for producing highly flame-retardant drum brake linings using economical flame-retardant materials. Summary of the invention
[0005] In view of this, the purpose of the present application is to provide a highly flame-retardant drum brake lining and a preparation method thereof. The preparation method of the highly flame-retardant drum brake lining comprises preparing a heat-resistant flame-retardant granular material before hot pressing, and then hot pressing the heat-resistant flame-retardant granular material and a friction material to make a highly flame-retardant drum brake lining. The prepared highly flame-retardant drum brake lining has a low cost and performs well in continuous braking tests without brake fire.
[0006] In order to achieve or at least partially achieve the above objectives, the present application provides the following technical solutions:
[0007] In a first aspect, the present application provides a method for preparing a highly flame-retardant drum brake lining, comprising:
[0008] The first step is to prepare a flame retardant matrix, mix the flame retardant matrix and then perform banburying to obtain a banburying material;
[0009] The second step is to roll the mixed material into a shape, and then crush the rolled product to obtain heat-resistant and flame-retardant particles;
[0010] The third step is to evenly distribute the heat-resistant and flame-retardant particles in the friction matrix material to obtain a mixed friction material;
[0011] The fourth step is to hot-press the mixed friction material and subsequently heat-cure it to obtain a highly flame-retardant drum brake lining.
[0012] In a second aspect, the present application provides a highly flame-retardant drum brake lining, which is prepared by the aforementioned preparation method.
[0013] Compared with the prior art, the technical solution provided by this application has at least the following beneficial effects:
[0014] 1. This application uses phosphorus-modified epoxy resin as a binder, aluminum hydroxide and zinc borate as flame retardants, barium sulfate, light magnesium oxide, and mica as a filler to prepare heat-resistant flame-retardant particles, wherein the binder and filler account for a large proportion of the mass of the heat-resistant flame-retardant particles, and the ductility is higher than that of the flame retardant, and the flame retardant is coated by the internal mixing and rolling process (flexible polymers and some fillers with good ductility are used, and the rigid flame retardant is coated to form a shell-core dispersed phase through the internal mixing and rolling process); the heat-resistant flame-retardant particles will not cause product stratification and bulging due to the precipitation of H2O molecules during hot pressing and heat curing, resulting in product scrapping; during the high-temperature braking process of the flame retardant, the binder in the coating layer quickly decomposes and loses the coating effect. At this time, the rapid precipitation of crystal water in the flame retardant reduces the ignition point of the friction material, and at the same time, it precipitates to the surface of the friction plate under the action of braking pressure to block the air, thereby curbing the fire.
[0015] 2. The highly flame-retardant drum brake lining prepared in the present application has a porous high-temperature resistant partitioning agent including kaolin, calcium silicate, and lightweight magnesium oxide added to the friction matrix material. During high-temperature braking, the high-temperature resistant partitioning agent can adsorb free radicals containing hydrogen and oxygen elements generated by the high-temperature decomposition of the friction matrix material, and at the same time form a protective film to wrap it, thereby blocking the oxygen required for combustion and curbing rapid ignition.
[0016] 3. In the flame retardant performance test of the highly flame retardant drum brake lining sample prepared in the present application, the oxygen index (OL) was greater than 35, and in the UL94 test, the burning time of the 10mm brake lining sample was less than 5S, both reaching the V-0 excellent standard. The highly flame retardant drum brake lining prepared in the present application was applied to heavy-duty commercial vehicles, and no brake fire incidents occurred in the continuous braking test on the long downhill section of Yunnan, Guizhou and Sichuan. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0018] Those skilled in the art will appreciate that, unless otherwise stated, the "said", "the", and "the aforementioned" used in the text of the present application may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present application means the presence of the features, steps, and operations, but does not exclude the presence or addition of one or more other features, integers, and steps.
[0019] The performance evaluation method of the flame retardant drum brake lining prepared in the embodiment of the present application is as follows:
[0020] (1) Friction coefficient: refer to GB / T34007-2017 Road Vehicle Brake Lining Friction Material Drag Test Method;
[0021] (2) Wear amount: refer to GB / T34007-2017 Road Vehicle Brake Lining Friction Material Drag Test Method;
[0022] (3) Oxygen index OL (10 mm): Plastics. Determination of combustion behavior by the oxygen index method. Part 2: Room temperature test;
[0023] (4) UL94 test (10mm): American UL94-flammability test of plastics for equipment and appliance components.
[0024] In the prior art, when using economical flame retardant materials such as aluminum hydroxide, magnesium hydroxide, zinc borate, etc., to prepare brake linings by hot pressing with friction materials, the hot pressing temperature is 180-200°C, and the maximum heat curing temperature is 200-220°C. The materials will be decomposed by heat to form water molecules, resulting in a high content of water molecules in the friction material of the brake lining, resulting in stratification and bubbling, and thus it is impossible to prepare qualified flame retardant brake lining products. In order to solve the above-mentioned processing bottleneck problem, the embodiment of the present application transforms the one-step hot pressing process into a new multi-step forming process. Before the hot pressing step, the new process first prepares a kind of heat-resistant flame-retardant particles. The heat-resistant flame-retardant particles play the following role in the hot pressing and high-temperature flame-retardant process of drum plates: under the conditions of hot pressing temperatures of 180-200°C and maximum thermal curing temperatures of 200-220°C, the wrapping layer completely covers the economical flame-retardant material to prevent the direct precipitation of crystalline water in the flame-retardant material into the friction matrix material; in addition, in the high-temperature braking section (500-600°C), the wrapping resin in the flame-retardant matrix material directly decomposes and loses the function of coating the economical flame-retardant material, and the crystalline water in the economical flame-retardant material is rapidly precipitated, reducing the temperature of the friction matrix material and the ignition point. The process will also absorb a large amount of heat, which will precipitate to the surface of the friction plate under the action of braking pressure to block the air and prevent the occurrence of fire.
[0025] Based on this, an embodiment of the present application provides a method for preparing a highly flame-retardant drum brake lining, the method comprising: (1) mixing a flame-retardant matrix and adding the mixture to an internal mixer for internal mixing, wherein the internal mixing time is 10 to 15 minutes, the internal mixing temperature range is 15 to 80°C, and the double-roll speed is 20 to 30 r / min to obtain an internal mixing material; (2) adding the internal mixing material prepared in step (1) to a roller mill for roller mixing, wherein the gap between the two rollers of the roller mill is less than 0.3 mm, and the roller mixing temperature is 90 to 95°C, and the obtained roller product is crushed to form heat-resistant flame-retardant particles; (3) uniformly distributing the heat-resistant flame-retardant base particles prepared in step (2) in a friction matrix material to obtain a mixed friction material; (4) hot-pressing the mixed friction material obtained in step (3) and subsequently heat-curing it to obtain a final highly flame-retardant drum brake lining.
[0026] In some embodiments, in (1), the components of the flame retardant matrix, calculated by weight, include 10-15 parts of phosphorus-modified epoxy resin, 5-10 parts of aluminum hydroxide, 4-8 parts of zinc borate, 30-40 parts of barium sulfate, 20-30 parts of light magnesium oxide, and 5-10 parts of mica; wherein the phosphorus-modified epoxy resin is used as a binder component, aluminum hydroxide and zinc borate are used as flame retardant components, and barium sulfate, light magnesium oxide and mica are used as fillers. The mass fraction of the flame retardant component in the flame retardant matrix is 10-15 parts, and the mass proportion of the binder and the filler in the flame retardant matrix is relatively large. In addition, the ductility of the binder and the filler is higher than that of the flame retardant, so that the phosphorus-modified epoxy resin is coated during the internal mixing and rolling process.
[0027] In certain preferred embodiments, in step (1), the components of the flame retardant matrix, calculated by weight, include 12 parts of phosphorus-modified epoxy resin, 8 parts of aluminum hydroxide, 7 parts of zinc borate, 30 parts of barium sulfate, 30 parts of light magnesium oxide, and 8 parts of mica.
[0028] In certain embodiments, in step (2), the thickness of the rolled product is 0.9 to 1.5 mm.
[0029] In certain embodiments, in step (2), the particle size of the heat-resistant flame-retardant particles obtained is 1.5 to 3 mm.
[0030] In certain embodiments, in step (3), the friction matrix material components include benzoxazine resin, glass fiber, mineral fiber, high temperature resistant separator, and friction performance regulator; the high temperature resistant separator includes kaolin, calcium silicate, and light magnesium oxide, and the high temperature resistant separator can absorb H2 and O2 generated by the decomposition of the friction matrix material at high temperature, and at the same time form a protective film to wrap it, thereby blocking the oxygen required for combustion and quickly curbing the fire; the friction performance regulator includes flake graphite, synthetic graphite, aluminum oxide, and zirconium silicate components.
[0031] In certain embodiments, in step (3), the components of the mixed friction material, calculated by mass percentage, include 10% to 15% benzoxazine resin, 8% to 10% glass fiber, 20% to 25% heat-resistant flame retardant particles, 10% to 15% mineral fiber, 10% to 16% kaolin, 7% to 12% calcium silicate, 7% to 12% light magnesium oxide, 4% to 6% flake graphite, 4% to 6% synthetic graphite, 2% to 4% aluminum oxide, and 2% to 4% zirconium silicate.
[0032] In certain embodiments, in step (4), the hot pressing temperature during the hot pressing molding process is 180-200°C, and the maximum temperature of the subsequent thermal curing is 200-220°C.
[0033] Based on this, an embodiment of the present application further provides a highly flame-retardant drum brake lining, which is prepared by the preparation method provided in the aforementioned embodiment.
[0034] The technical solution of the present application and the technical effects achieved are described in detail below through more specific embodiments.
[0035] Example 1
[0036] This embodiment provides a method for preparing a highly flame-retardant drum brake lining, and the specific steps are as follows:
[0037] (1) preparing a flame retardant matrix, wherein the components thereof include 12 parts by weight of phosphorus-modified epoxy resin, 8 parts by weight of aluminum hydroxide, 7 parts by weight of zinc borate, 30 parts by weight of barium sulfate, 30 parts by weight of light magnesium oxide, and 8 parts by weight of mica; adding the prepared flame retardant matrix to a 100L plowshare mixer for mixing at a stirring speed of 50 r / min for a mixing time of 5 min; adding the obtained mixture to a 60L internal mixer for internal mixing at a mixing time of 12 min at a mixing temperature range of 15 to 80° C., a top bolt pressure of 0.6 MPa, and a double roller speed of 20 r / min to obtain an internal mixing material;
[0038] (2) adding the mixed material obtained in (1) to a double-motion roller mill, adjusting the gap between the two rollers to 0.2 mm and the roller temperature to 95° C.; obtaining a roller-refined product with a thickness of 1 to 1.2 mm, and crushing the roller-refined product to obtain heat-resistant flame-retardant particles X1, with a particle size controlled at 2 to 3 mm;
[0039] (3) The heat-resistant flame-retardant particles X1 obtained in (2) were mixed with the friction base material Y1 at a mass ratio of 24:76 to obtain a mixed friction material, the mass fractions of which are shown in Table 1 below;
[0040] Table 1
[0041]
[0042] (4) hot pressing the mixed friction material in (3) at 180°C, and then at 200°C
[0043] The product is thermally cured to obtain a highly flame-retardant drum brake lining Z1.
[0044] Example 2
[0045] This embodiment provides a method for preparing a highly flame-retardant drum brake lining, and the specific steps are as follows:
[0046] (1) preparing a flame retardant matrix, wherein the components thereof include 12 parts by weight of phosphorus-modified epoxy resin, 8 parts of aluminum hydroxide, 7 parts of zinc borate, 30 parts of barium sulfate, 30 parts of light magnesium oxide, and 8 parts of mica; adding the prepared flame retardant matrix to a 100L plowshare mixer for mixing at a stirring speed of 50r / min for a mixing time of 5min; adding the obtained mixture to a 60L internal mixer for internal mixing at a mixing time of 10min, a internal mixing temperature range of 15 to 80°C, an upper ejector pressure of 0.6MPa, and a double roller speed of 25r / min to obtain an internal mixing material;
[0047] (2) adding the mixed material obtained in (1) to a double-motion roller mill, adjusting the gap between the two rollers to 0.2 mm and the roller temperature to 90° C.; obtaining a roller-refined product with a thickness of 1 to 1.2 mm, and crushing the roller-refined product to obtain heat-resistant flame-retardant particles X2, with a particle size controlled at 2 to 3 mm;
[0048] (3) The heat-resistant flame-retardant particles X2 obtained in (2) were mixed with the friction base material Y2 at a mass ratio of 20:80 to obtain a mixed friction material, the mass fractions of which are shown in Table 2 below;
[0049] Table 2
[0050]
[0051] (4) The mixed friction material in (3) is hot pressed at 190° C. and then heat cured at 210° C. to obtain a highly flame-retardant drum brake lining Z2.
[0052] Example 3
[0053] This embodiment provides a method for preparing a highly flame-retardant drum brake lining, and the specific steps are as follows:
[0054] (1) preparing a flame retardant matrix, wherein the components thereof include 12 parts by weight of phosphorus-modified epoxy resin, 8 parts of aluminum hydroxide, 7 parts of zinc borate, 30 parts of barium sulfate, 30 parts of light magnesium oxide, and 8 parts of mica; adding the prepared flame retardant matrix to a 100L plowshare mixer for mixing at a stirring speed of 50r / min for a mixing time of 5min; adding the obtained mixture to a 60L internal mixer for internal mixing at a mixing time of 15min, a internal mixing temperature range of 15 to 80°C, an upper ejector pressure of 0.7MPa, and a double roller speed of 30r / min to obtain an internal mixing material;
[0055] (2) adding the internally mixed material obtained in (1) to a double-motion roller mill, adjusting the gap between the two rollers to 0.15 mm and the roller temperature to 92° C.; obtaining a roller-refined product with a thickness of 0.9 to 1 mm, and crushing the roller-refined product to obtain heat-resistant flame-retardant particles X3, with a particle size controlled at 1.5 to 2 mm;
[0056] (3) The heat-resistant flame-retardant particles X3 obtained in (2) were mixed with the friction base material Y3 at a mass ratio of 24:76 to obtain a mixed friction material, the mass fractions of which are shown in Table 3 below;
[0057] Table 3
[0058]
[0059]
[0060] (4) The mixed friction material in (3) is hot pressed at 200° C. and then heat cured at 220° C. to obtain a highly flame-retardant drum brake lining Z3.
[0061] Comparative Example 1
[0062] This comparative example provides a method for preparing a drum brake lining, and the specific steps are as follows:
[0063] (1) Prepare friction matrix material Y4, the mass fractions of its components are as follows;
[0064] Table 4
[0065]
[0066] (2) The friction matrix material Y4 is hot-pressed at 160°C to produce a drum brake lining Z4.
[0067] The flame retardant performance of the highly flame-retardant drum brake linings Z1, Z2, Z3 prepared in Examples 1 to 3 and Z4 prepared in Comparative Example 1 were tested respectively, and the test items included friction coefficient, wear amount, oxygen index OL (10 mm) and UL94 test (10 mm); wherein the friction coefficient is the main functional parameter of the brake lining, directly affecting the magnitude of the braking torque, and is an important parameter for ensuring driving safety. The friction coefficient design value of the conventional drum friction lining is between 0.35 and 0.45, which is to ensure sufficient braking torque to ensure driving safety, and not to generate braking noise due to a large friction coefficient. The noise affects driving comfort; the wear test is an important indicator for examining the service life of the friction plate. The wear test of the small sample can be used to infer the service life of the friction plate with this formula; the oxygen index OL refers to the minimum oxygen concentration required for the material to burn with a flame in an oxygen-nitrogen mixed gas flow under specified conditions, and is an important indicator of the flame retardant performance of the material; the UL94 test refers to heating and burning a sample of a specific thickness on an alcohol lamp in an air atmosphere, then removing the fire source and recording the time required for the material to extinguish itself. The grade assessment is: <10S is V-0, 10~20S is V-1, and 20~30S is V-2.
[0068] The flame retardant performance test results are shown in Table 5 below:
[0069] Table 5
[0070]
[0071] From the analysis of the results shown in Table 5, the friction coefficients of the highly flame-retardant drum brake linings Z1, Z2, and Z3 prepared in the embodiment and the drum brake lining Z4 prepared in the comparative example are all in the range of 0.35 to 0.45, and the wear amounts of Z1, Z2, and Z3 are substantially equivalent to that of Z4, which indicates that the friction performance of the highly flame-retardant drum brake linings provided in the embodiments of the present application will not be affected by the addition of flame-retardant materials.
[0072] It can be seen from Table 5 that the oxygen index OL (10mm) of the highly flame-retardant drum brake linings prepared in Examples 1 to 3 is above 35, while the OL (10mm) of the drum brake linings prepared in the comparative example is only 31. In addition, compared with the UL94 test (10mm) results, the burning time of the highly flame-retardant drum brake linings prepared in the examples is below 4S, which is much lower than the burning time (16S) of the drum brake linings in the comparative example. The UL94 test (10mm) grade of the highly flame-retardant drum brake linings prepared in the examples all reaches the optimal V-0 grade, which is better than the UL94 test (10mm) grade (V-1 grade) of the drum brake linings prepared in the comparative example. The above results show that the highly flame-retardant drum brake linings prepared in the examples of the present application have excellent flame retardant properties.
[0073] The present application is described in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the present application and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present application, several improvements and modifications can be made to the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.
Claims
1. A method for preparing a highly flame-retardant drum brake lining, characterized in that: The following steps are involved: The first step is to prepare a flame retardant matrix, mix the flame retardant matrix and then perform banburying to obtain a banburying material; The second step is to roll the mixed material into a shape, and then crush the obtained roll-refined product to obtain heat-resistant flame-retardant particles; The third step is to evenly distribute the heat-resistant and flame-retardant particles in the friction matrix material to obtain a mixed friction material; The fourth step is to hot-press the mixed friction material and subsequently heat-cure it to obtain a highly flame-retardant drum brake lining.
2. The preparation method according to claim 1, characterized in that: In the first step, the components of the flame retardant matrix, calculated by mass, include 10-15 parts of phosphorus-modified epoxy resin, 5-10 parts of aluminum hydroxide, 4-8 parts of zinc borate, 30-40 parts of barium sulfate, 20-30 parts of light magnesium oxide, and 5-10 parts of mica.
3. The preparation method according to claim 2, characterized in that: The components of the flame retardant matrix, calculated by weight, include 12 parts of phosphorus-modified epoxy resin, 8 parts of aluminum hydroxide, 7 parts of zinc borate, 30 parts of barium sulfate, 30 parts of light magnesium oxide, and 8 parts of mica.
4. The preparation method according to claim 1, characterized in that: In the first step, the mixing temperature is 15-80° C., and the mixing time is 10-15 min. In the second step, the mixing temperature during the rolling forming process is 85-95° C.
5. The preparation method according to claim 1, characterized in that: In the second step, the thickness of the rolled product is 0.9-1.5 mm.
6. The preparation method according to claim 1, characterized in that: The particle size of the obtained heat-resistant flame-retardant particles is 1.5 to 3 mm.
7. The preparation method according to claim 1, characterized in that: In the third step, the friction matrix material components include benzoxazine resin, glass fiber, mineral fiber, high temperature resistant separator, and friction performance regulator; the high temperature resistant separator includes kaolin, calcium silicate, and light magnesium oxide; the friction performance regulator includes flake graphite, synthetic graphite, aluminum oxide, and zirconium silicate components.
8. The preparation method according to claim 7, characterized in that: The components of the mixed friction material, calculated by mass percentage, include 10% to 15% benzoxazine resin, 8% to 10% glass fiber, 20% to 25% heat-resistant flame retardant particles, 10% to 15% mineral fiber, 10% to 16% kaolin, 7% to 12% calcium silicate, 7% to 12% light magnesium oxide, 4% to 6% flake graphite, 4% to 6% synthetic graphite, 2% to 4% aluminum oxide, and 2% to 4% zirconium silicate.
9. The preparation method according to claim 1, characterized in that: The hot pressing temperature during the hot pressing forming process is 180-200°C, and the maximum temperature of the subsequent thermal curing is 200-220°C.
10. A highly flame-retardant drum brake lining, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Fire retardant composition
CN104086878A
Calcium carbonate whisker reinforced resin-rubber base friction material and preparation method therefor
CN105111675A
Environmentally-friendly friction material and preparation process thereof
CN110003854A
Flame-retardant friction body, brake pad / brake shoe and preparation method of brake pad / brake shoe
CN111911572A
Fire-retarded epoxy resin composition, its preparing method and use
CN1339534A